Pelatihan Pembuatan Video Pembelajaran Dan Kuis Interaktif Serta Penggunaan Macromedia Flash Bagi Guru-Gurupenjasorkes Di Kabupaten Sijunjung - Sri Gusti Handayani; Anton Komaini; Yulifri Yulifri (Pusat Kajian Pendidikan Olahraga, Kesehatan dan Rekreasi Jurusan Pendidikan Olahraga Fakultas Ilmu Keolahragaan Uiveristas Negeri Padang Jl. Prof. Hamka, Air Tawar Padang 25131 Telp. 0751-7059901, 2020)
The problem in this activity is the physical education teachers in Sijunjung Regency complained about the difficulty of making materials for online teaching, besides that they have run out of ideas so that PBM PJOK becomes interesting and interactive even though it is carried out online. And PJOK teachers in Sijunjung Regency are still not optimally making interactive learning videos and quizzes. These constraints, it will certainly hinder the PBM process. The target of this activity is Physical Education teachers in Sijunjung Regency. The results of this activity were the increased understanding and skills of Physical Education teachers in Sijunjung Regency in making instructional videos, interactive quizzes and the use of Macromedia flas. The method to be used in this service activity is through direct or indirect training